An Analysis of 'Migrant-intensity' in India and Indonesia: Seeing Internal Migration Patterns through a Place-based Lens. (March 2017) - Randolph, Gregory F.; Naik, Mukta
Emerging economies are witnessing the large-scale movement of internal migrants. While the popular discourse on internal migration imagines migrants from villages flooding into the large metropolis, scholarship is increasingly emphasizing the existence of multiple migration pathways, as well as the emergence of more dispersed patterns of urbanization. To root these discussions in particular geographies, this paper introduces the concept of 'migrant-intensity' as an empirical way of understanding the places that experience migration in the most profound and transformative ways—where the challenges and opportunities inherent in transience and mobility are most apparent. Analyzing census data from India and Indonesia, we show that 'migrant-intensity'—a measure of in- and out-migrant concentration—is highest in a diverse set of non-metropolitan spaces, including secondary and tertiary cities and 'rurban' geographies. We argue that migrant-intensity as an empirical tool can advance scholarship on complex migration patterns by identifying the places at the crossroads of migrant pathways. Moreover, it can help planners and policymakers to address unique challenges, opportunities and constraints of migrant-intensive places.